Confronting Iraq : U.S. policy and the use of force since the Gulf War - Byman, Daniel, 1967- (RAND, 2000)
Although Iraq remains hostile to the United States, Baghdad has repeatedly compromised, and at times caved, in response to U.S. pressure and threats. An analysis of attempts to coerce Iraq since Desert Storm reveals that military strikes and other forms of pressure that threatened Saddam Husayn's relationship with his power base proved effective at forcing concessions from the Iraqi regime. When coercing Saddam or other foes, U.S. policymakers should design a strategy around the adversary's "center of gravity" while seeking to neutralize adversary efforts to counter-coerce the United States and appreciating the policy constraints imposed by domestic politics and international alliances